Potenciais e demandas para o desenvolvimento da agroecologia na região da bacia do Alto Sorocaba-Médio Tietê: ações, instituições e inserção junto à agricultura familiar - Gonçalves, Pedro Kawamura (Universidade Federal de São Carlos, 2012)
The current situation of social and environmental degradation observed in rural areas of Brazil derives from a historical multidimensional process involving strong political and economic interests, where the techniques and ideas of the "Green Revolution" justify the propagation of inequities in land ownership and agricultural policies country. This process culminates in the current title of world's largest consumer of pesticides, coupled with the rapid advancement of transgenic seeds, increasingly threatening the autonomy of agriculture and food security in the country. Faced with this, Agroecology emerges as a science engaged in the transformation of social reality in the field, adding knowledge, multidisciplinary actors and social movements. This work was conducted in the Upper Sorocaba/ Middle Tietê Basin, a region with a strong presence of family farming. We sought to understand the situation of family farming and the insertion of Agroecology among this audience. Also sought to systematize learnings and indicate preferential paths for the continuity of actions involving the thematic of Agroforestry Systems, agroecological extension and environmental regularization of farms, as important components of a process of agroecological transition. There has been a considerable advance in associativism in the region, driven primarily by governmental programs of institutional purchase (PAA and school meals), which also show the potential to stimulate the transition to organic agriculture. Virtually no other public policy is recognized as important for this audience. The failure of the structure of public ATER is recognized, and noted a decrease in their staff in recent years. After decades of difficulties in marketing , lack of political support , lack of credit and cultural devaluation, the farmer 's children launch themselves to work in the city , endangering the reproduction of family farming . Faced with this, the main strategies and demands of farmers groups converge to the viability of the market , the primary source of income for families . Although there are examples of technical and economic success of pioneer farmers in organic agriculture in the region, we note that few institutions have actions to stimulate this type of agriculture, prevailing prejudices and misinformation about its technical and economic feasibility. The study of the projects showed that third-sector institutions and universities are responsible for innovative actions in agroforestry systems as forms of land use and for the recovery of degraded areas. It is considered that more continuous actions are needed to consolidate this form of land use, which has the ability to bring economic, social and environmental benefits in the short, medium and long term for the families involved. The group of institutions that have recently articulated around Sorocabana Agroecology Network show potential to advance in the aspects of teaching, research and extension in sustainable agriculture, to deal with regional demands to advancing this paradigm with the family farm, which are: need for certification; establishing solidarity markets, consolidation and exchange experiences; technical monitoring of farmers.
Demands and potential for the agroecology development on the middle Tietê -High Sorocaba Basin Region: shares, institutions and insertion into the family farm
Keywords: Agroecologia; Extensão rural - assistência técnica; Tietê, Rio, Bacia (SP); Sistemas agroflorestais; Agricultura familiar; CIENCIAS AGRARIAS